[Afisz. Incipit] Dziennik Bałtycki przynosi ... (Gdynia : [wydawca nieznany], 1949)
Afisz reklamujący Dziennik Bałtycki.
Keywords: Prasa -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła